Reforma Kelembagaan Dalam Kebijakan Reforma Agraria Era Joko Widodo-Jusuf Kalla - Luthfi, Ahmad Nashih (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Abstract: The development of agrarian reform institution is one of the indicators of the government’s seriousness in agrarian policy. The extent to which the government realizes the gravity of agrarian problems requires solution through agrarian reform are reflected through the existence of a special implementing institution. The Jokowi-JK government succeeded in creating two institutions called the Team of Identification and Inventoritation and the Agrarian Reform Task Force. Both are created by different presidential regulations. Under qualitative approach on policy review method, this article examines the institutions and implementation of agrarian reform at the national level and accompanied by a field study in Sigi Regency to illustrate the dynamics of the relationship between civil society and the state in the policy. This article concludes that in developing the Agarian Reform Institution the government undertook a strategic compromise in the midst of the sectoralization of existing ministries. It created in the midst of the sectoralization situation of existing ministries/ institution. The institutions unable to be free from sectoral burden; and the national government think that the urgency of the agrarian problem is the form of ensuring land rights through accelerating land registration, outbid agrarian inequality and agrarian conflict Uniquely, this legalization policy is organized within the framework of agrarian reform. Keywords: institution, agrarian reform, sectoralization, compromise Intisari: Pembangunan kelembagaan Reforma Agraria merupakan cermin dan indikator keseriusan pemerintah dalam kebijakan agraria. Sejauh mana pemerintah memahami dan menyadari kegawatan masalah yang memerlukan pemecahan melalui Reforma Agraria terefleksikan melalui dibentuknya suatu lembaga pelaksana khusus. Pemerintah Jokowi-JK berhasil mewujudkan dua lembaga yang bernama Tim Inver dan Gugus Tugas Reforma Agraria. Keduanya dinaungi oleh peraturan presiden yang berbeda. Dengan pendekatan kajian kebijakan yang bersifat kualitatif, artikel ini menelaah kelembagaan dan pelaksanaan Reforma Agraria di aras nasional disertai kajian lapangan di Kabupaten Sigi untuk memberi ilustrasi dinamika hubungan antara masyarakat sipil dan negara di dalam kebijakan tersebut. Artikel ini menyimpulkan bahwa didalam membangun kelembagaan reforma agaria pemerintah melakukan strategi kompromi di tengah situasi sektoralisasi kementerian/lembaga yang ada; serta pemahaman pemerintah atas kegentingan masalah berupa pemastian hak atas tanah melalui percepatan pendaftaran tanah, alih-alih soal ketimpangan agraria dan konflik yang menyertainya. Uniknya, kebijakan legalisasi ini diskemakan dalam kerangka Reforma Agraria. Kata kunci: kelembagaan, Reforma Agraria, sektoralisasi, kompromi